2022
DOI: 10.21608/jacb.2022.118365.1018
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of Four Egyptian Plant Species using some Molecular Markers Techniques RAPD, ISSR, and SCoT

Abstract: Four plant species belonging to the family Lamiaceae were assessed with different molecular markers using five RAPD, six inter simple sequence repeats (ISSR), and six start codon targeted (SCoT) primers to detect their levels of genetic diversity. The RAPD primers identified a total of 41 amplified bands, while all primers inducing five unique markers among the four species used in this study, furthermore the polymorphism percentage reached to 73.71%. ISSR primers generated 31 amplified bands including eight u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…The above-obtained results suggested that the SCoT marker can be used to effectively detect the molecular alterations among treated spinach plants. These results are in harmony with previously obtained in Mangiferea indica (Luo et al 2010 ), in Arachis hypogaea (Xiong et al 2011 ), in Echinacea (Jedrzejczyk 2020 ), in Vitis uinifera (Ahmed et al 2021 ), in Lamiaceae species (Ahmed et al 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…The above-obtained results suggested that the SCoT marker can be used to effectively detect the molecular alterations among treated spinach plants. These results are in harmony with previously obtained in Mangiferea indica (Luo et al 2010 ), in Arachis hypogaea (Xiong et al 2011 ), in Echinacea (Jedrzejczyk 2020 ), in Vitis uinifera (Ahmed et al 2021 ), in Lamiaceae species (Ahmed et al 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…The rationale for the use of RAPD molecular markers for Lamiaceae species is supported by several current studies (Chowdhury et al, 2017;Ahmed and Al-Sodany, 2019;Saha et al, 2020;Sunar et al, 2020;Zhend et al, 2021;Ahmed et al, 2022).…”
Section: Resultsmentioning
confidence: 92%